The use of Tantum Verde® at the stages of complex treatment of patients with generalized periodontitis - Печковська, Ірина Михайлівна; Несин, Олександр Федорович; Печковський, Костянтин Євгенович; Відерська, Ганна Володимирівна; Тімохіна, Тетяна Олександрівна (Actual Dentistry, 2019)
Relevance. Generalized periodontitis is the most common periodontal disease in the human adult population. In its pathogenetic treatment, the reasonable use of complex action agents that produce local anti-inflammatory, reduce swelling and pain of periodontal soft tissues, also have antimicrobial properties. One of them is Tantum Verde® – a local non steroid drug based on hydrochloride benzydamine. The aim of this study was to evaluate the efficiency of the use of the drug Tantum Verde® at stages of complex treatment of generalized periodontitis. Research results. Comprehensive treatment was carried out in 34 patients with generalized periodontitis aged 27–54 years. 17 patients of the research group at all stages (phases) of the treatment were additionally used the drug Tantum Verde®. After the first (conservative) treatment phase, the disappearance or significant decrease in clinical signs of inflammation occurred faster in the patients of the experimental group than in the patients of the comparison group (on average, after 5.1 and 5.9 visits). se of Tantum Verde® on second phase (surgical) treatment reduced pain after surgery, improved the hygienic condition of the sutures and accelerated the healing of periodontal sites after surgery. On the third (orthopedic) phase of treatment, Tantum Verde® reduced the risk of inflammation and gum recession at the gum rim of coronal tires. Conclusions. The use of drug, Tantum Verde®, in the complex treatment of patients with generalized periodontitis accelerates the disappearance of signs of inflammation and reduces the average number of visits to one visit during the therapeutic treatment phase; reduces the inflammatory response of tissues, improves hygiene, accelerates healing and removal of sutures by 1–1.5 days in the phase of surgical treatment; reduces patient's pain during preparation, prevents reactive inflammation for invasive intervention, minimizes the risk of gum recession at the gum edge of crowns during orthopedic splint of teeth. Key words: Tantum Verde®, generalized periodontitis, complex treatment.